2016
DOI: 10.1002/14651858.cd007202.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of restricted pacifier use in breastfeeding term infants for increasing duration of breastfeeding

Abstract: Pacifier use in healthy term breastfeeding infants, started from birth or after lactation is established, did not significantly affect the prevalence or duration of exclusive and partial breastfeeding up to four months of age. Evidence to assess the short-term breastfeeding difficulties faced by mothers and long-term effect of pacifiers on infants' health is lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
7

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 28 publications
4
38
0
7
Order By: Relevance
“…We found 16 studies done outside Iran (17, 18, 20-23, 25, 29-37), and 3 studies from Iran, that fulfilled our inclusion criteria (15,19,27). From the researches done abroad, (with accessible full texts), eight studies, including a meta-analysis, reported a deleterious effect of pacifiers on breastfeeding (17)(18)(19)(20)(21)(22)(23)30); five papers refuted these observations (25,(33)(34)(35)37) and findings from four surveys were inconclusive (24,31,32,36). All three studies from Iran claimed that pacifier use is associated with decreased duration of EBF/predominant breast feeding and early introduction of the bottle (5,19,27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found 16 studies done outside Iran (17, 18, 20-23, 25, 29-37), and 3 studies from Iran, that fulfilled our inclusion criteria (15,19,27). From the researches done abroad, (with accessible full texts), eight studies, including a meta-analysis, reported a deleterious effect of pacifiers on breastfeeding (17)(18)(19)(20)(21)(22)(23)30); five papers refuted these observations (25,(33)(34)(35)37) and findings from four surveys were inconclusive (24,31,32,36). All three studies from Iran claimed that pacifier use is associated with decreased duration of EBF/predominant breast feeding and early introduction of the bottle (5,19,27).…”
Section: Resultsmentioning
confidence: 99%
“…A recent Cochrane review done to determine the effect of restricting the use of pacifiers and to compare it with unrestricted use on the duration of breastfeeding, found no significant difference in the rate of EBF in healthy breast feeding babies at 3 and 4 months of age, (RR 0.99; 95% CI: 0.93 -1.05 and RR 0.99; CI: 0.92 -1.06, respectively) (33). This review has included 2 studies in their final analysis, one from Kramer et al in 2001 and the other from Jenik et al in 2009 (35,37).…”
Section: Resultsmentioning
confidence: 99%
“…The use of a pacifier has been reported as an indicator of maternal difficulty in BF management and it signals their willingness to wean (26). The association between pacifier use and duration of AME presents conflicting results, although recent systematic reviews concluded that the use of pacifier associated with the shortest time of AME (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature the use of a pacifier also has a negative impact on the duration of breastfeeding and breast milk intake (Jaafar, 2012). Use of a pacifier causes a decrease in milk production by weakening the power of sucking and for this reason lead to discontinuation of breastfeeding and reduce the duration of infants'breast milk intake (Bakiler et al, 2005).…”
Section: Discussionmentioning
confidence: 99%